The Influence Leader Member Exchangeand Work Commitment towards Employee Performance through Mediation Organization Citizenship Behavior - Heri Prasetyo; Honorata Ratnawati DP; Sri Suyati (Yayasan Payungi Smart Madani, 2025)
This study aims to analyze the influence Leader Member Exchange and work commitment to the performance of employees of the Semarang Maritime Polytechnic (PIP) both directly and indirectly through Organizational Citizenship Behavioras an intervening variable. The population used was all employees at the Semarang Maritime Polytechnic (PIP) with a total of 168 employees, the number of samples used was 120 respondents, with the sampling technique used was proportionate random sampling. The data source used was primary data, with data collection using a questionnaire. The data analysis technique used path analysis and the mediation test used the Sobel test. The results of the study showed that Leader Member Exchange has a positive and significant effect on Organizational Citizenship Behavior, and work commitment has a positive and significant influence on Organizational Citizenship Behavior. Leader Member Exchange has a positive and significant effect on employee performance, work commitment has a positive and significant effect on employee performance, and Organizational Citizenship Behavior has a positive and significant effect on employee performance. From the results of the mediation test with the Sobel test, it was obtained that Organizational Citizenship Behavior can mediate the influence Leader Member Exchange on employee performance. Organizational Citizenship Behavior can mediate the influence of work commitment on employee performance.